Facilitators And Barriers to Hypertension Control, Fol-lowing the Implementation of India Hypertension Con-trol Initiative (IHCI) In Thiruvananthapuram District - A Qualitative Study - Balamurali V; Lavanya P; Kumar Sumit (Medsci Publications, 2022)
Background: India Hypertension Control Initiative (IHCI) was launched in 2017 to improve the control rate of hypertensive patients on treatment. Thiruvananthapuram was one among the 26 districts in the country where the program was initially rolled out. Methods: A qualitative cross-sectional study was conducted among stakeholders involved in the implementation of IHCI of Thiruvananthapuram district. Purposive sampling method was used for selection of samples. A total of 25 in-depth interviews were carried out. Results: The major facilitators which propelled hypertension control were uniformity in drug prescription, proper documentation of patient data along with indicators for measuring control rates and defaulter tracking mechanism. Clinical inertia among doctors, increased workload and sending of bystanders for monthly follow-up are the major barriers that affected hypertension control. Conclusions: Replication of good practices performed under IHCI into similar health settings or programs can be encouraged. Apart from the few barriers seen at the program level, the already existing barriers at the health system level need to be addressed immediately through efforts such as e-Health incorporation, trainings .